Academic Stress among Adolescents of Rural Nepal: A Community-based Cross-Sectional Study - Pant, Suman; Rajbhandari, Bibek; Gurung, Minani; Poudel, Lisasha; Maharjan, Ashmita; Nepal, Sujita; Thapa, Tek Bahadur; Malla, Nabina; Lama, Tashi; Sharma, Dikshya; Gurung, Chandani; Parajuli, Yubraj; et al. (Journal of Nepal Health Research Council, 2023)
Background: Adolescents are in the transition phase between childhood and adulthood. Their mental health influences many aspects in their life as they go through many physical and emotional changes. Adolescent mental health is harmed by changes in emotional and physical state, as well as increased academic pressure. This study aimed to assess academic stress and its associated factors among adolescents in rural Nepal. Methods: A community-based cross-sectional survey was conducted among 424 adolescents residing in Karnali Province, Nepal. Academic stress was measured using Student Assessing Academic Stress. Multivariate logistic regression analysis was used to examine associated factors at the significance level of 0.05. Results: Of the total students, 19.8% had moderate academic stress and 2.4% of them had high academic stress. Female students had thrice higher odds of having academic stress as compared to male students (Adjusted Odds Ratio:3.47; 95% Confidence Interval:1.91to 6.31, p-value:<0.001). Grade 10 students had higher odds of having academic stress as compared to grade 9 (Adjusted Odds Ratio:2.02; 95% Confidence Interval:1.13 to 3.61, p-value:0.017). Students of literate mothers were more likely to experience academic stress than those with illiterate mothers (Adjusted Odds Ratio:0.53; 95% Confidence Interval:0.29 to 0.96, p-value:0.036). Students with unsatisfactory academic performance had thrice higher odds of having academic stress as compared to students with satisfactory academic performance (Adjusted Odds Ratio:3.12; 95% Confidence Interval:1.46 to 6.67, p-value:<0.003). Conclusions: The findings of the study showed that high school students have academic stress, which is related to many factors at home and school. Understanding academic stress and parents and teachers providing the best support to the students could help lessen the burden. Keywords: Academic stress; adolescents; Nepal; prevalence